2019
DOI: 10.1371/journal.pntd.0007638
|View full text |Cite
|
Sign up to set email alerts
|

Progression of scarring trachoma in Tanzanian children: A four-year cohort study

Abstract: Background Trachoma is a progressive blinding disease initiated by infection of the conjunctiva with Chlamydia trachomatis . Repeated infections are thought to cause chronic inflammation, which drives scarring, leading to in-turning of the eyelids. The relationship between C . trachomatis , clinical inflammation and scarring development in children is not fully understood due to a paucity of longitudinal studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 31 publications
(32 reference statements)
2
37
1
Order By: Relevance
“…A detailed description of the longitudinal study design and primary outcomes has been published elsewhere (4,9,10). Briefly, of the 666 eligible children, 616 were enrolled in the cohort study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the longitudinal study design and primary outcomes has been published elsewhere (4,9,10). Briefly, of the 666 eligible children, 616 were enrolled in the cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…Prior analysis of the cohort data set indicated that the marginal association between C. trachomatis infection and 4-year scarring progression was mediated through TP, suggesting that an individual's response to infection-rather than simply the presence or absence of infection alone-determines their risk of scarring sequelae (9). In order to investigate this further, random effects regression models were performed for each gene in turn; these included an interaction term between scarring progression status and C. trachomatis infection in order to determine whether scarring progressors responded differently to infection relative to nonprogressors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjunctival swabs were collected as previously described using sterile polyester-tipped swabs [7,8]. The rst swab was collected into 250µl RNA later and was used elsewhere [7][8][9], whilst the second swab was collected dry and stored at -80°C until used in this study. 0.5% of swabs collected were 'air' control swabs in order to test for eld and laboratory contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Conjunctival swabs were collected as previously described using sterile polyester-tipped swabs [7,8]. The rst swab was collected into 250 ml RNA later and was used elsewhere [7][8][9], whilst the second swab was collected dry and stored at -80 °C until used in this study. 0.5% of swabs collected were 'air' control swabs in order to test for eld-and laboratory contamination.…”
Section: Methodsmentioning
confidence: 99%